Unveiling comparative bioactivities of Kratom leaf extracts obtained via maceration and ultrasonic techniques: antioxidant, antimicrobial, and antibiofilm effects with molecular docking of Q-ToF-LCMS identified compounds and ADMET prediction - Begum, Taslima; Arzmi, Mohd Hafiz; Helal Uddin, A.B.M.; Rofiee, Mohd Salleh; Ali Shah, Syed Adnan; Parveen, Humaira; Mukhtar, Sayeed; Ahmed, Qamar Uddin (Scientific Scholar, 2025)
Traditional medicinal practices across Southeast Asia, particularly in Thailand and Malaysia, have long utilized Kratom (Mitragyna speciosa) leaves for the treatment of various health conditions. However, the medicinal potential of this plant has not been properly examined. Hence, this research study was performed to explore the antioxidant, antimicrobial, and antibiofilm properties of Kratom leaf extracts, along with the identification of biologically active phytochemical components via quadrupole time-of-flight liquid chromatography-mass spectrometry (Q-ToF-LCMS) and in silico approaches to assess their potential as new antibacterial agents. Accordingly, 12 leaf extracts were prepared and categorized into three distinct groups based on extraction techniques: maceration, ultrasound-assisted extraction (UAE), and fractionation. Each extract was subjected to phytochemical screening, including assessments of total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity via DPPH radical scavenging and Ferric Reducing Antioxidant Power Assay (FRAP) reduction assays. In addition, antibacterial and antibiofilm activities were evaluated using disc diffusion, broth microdilution, and biofilm inhibition assays against Escherichia coli, Streptococcus mutans, and Staphylococcus aureus. Ultimately, 100% methanol extracts, obtained through both maceration and ultrasonic extraction, exhibited the highest antioxidant activity across all tested parameters. Specifically: maceration (100% Methanol M) (TPC: 257.46 ± 1.32 mg GAE/g extract; TFC: 50.75 ± 0.24 mg QE/g extract; FRAP: 2103.46 ± 5.67 mg AAE/g extract, DPPH IC50: 7.94 ± 0.12 μg/mL), and ultrasonic extraction (100% Methanol U) (TPC: 340.99 ± 2.38 mg GAE/g extract; TFC: 62.95± 0.77 mg QE/g extract; FRAP: 2365.99 ± 3.39 mg AAE/g extract, DPPH IC50: 7.57 ± 0.24 μg/mL). Among the fractions derived from 100% methanol maceration, the ethyl acetate fraction demonstrated superior antioxidant activity compared to the corresponding alkaloid fraction, with the following values: (TPC: 337.00 ± 19.60 mg GAE/g extract; TFC: 57.72 ± 3.79 mg QE/g extract; FRAP: 2981.70 ± 40.6 mg AAE/g extract, DPPH IC50: 15.03 ± 0.54 μg/mL). The ethyl acetate fraction exhibited the highest activity with MICs of S. aureus (1.25 mg/mL) and S. mutans (2.5 mg/mL). Compounds identified through Q-ToF LC-MS analysis demonstrated favorable molecular interactions and strong binding affinities with the target protein of S. aureus (PDB ID: 3U2D) as revealed by molecular docking studies. Finally, 6-hydroxyluteolin 5-rhamnoside, kaempferol 3-(6''-p-coumarylglucoside)-7-glucoside, 6-hydroxyluteoin-7-(6'''-p-coumarylsophoroside), 8-hydroxyluteolin 8-glucoside, luteolin 7-rhamnosyl(1-6)galactoside, along with 10-hydroxyyohimbine showed great potential as leads for developing new antibacterial agents.